Droga rozeznawania. Pomoc dla osób rozwiedzionych żyjących w nowych związkach - Krajczyński, Jan (Ius Matrimoniale, 2017)
The author of the paper raises the question touched on by Pope Francis in his Amoris laetitia Apostolic Exhortation i.e. the way of discernment for divorced people living in new relationships. He restricts his argument to three fundamental issues which are: 1) discernment of incorrect situations with their character, motives and aims, 2) human and Christian rules; which are to be respected while discerning incorrect situation, 3) ways for providing answer to God and developing among restrictions, suitable to effects of discernment. The content of the presentation was rendered during the 375 Polish Episcopal Conference in Warsaw on 13 March 2017. This conference was attended not only by Polish bishops but also by 17 bishops from abroad and representatives of 15 Bishop Conference.